Synthesis, Structural Studies and Antimicrobial Evaluation of Nickel(II) Bis-Complex of Schiff Base of S-Benzyldithiocarbazate - Abdul Manan, Mohd Abdul Fatah; Mohammat, Mohd Fazli (Trends in Sciences, 2022)
A tridentate nitrogen-oxygen-sulfur (NOS) S-benzyl(2-oxoindolin-3-ylidene)dithiocarbazate, HSBISA (HL1) ligand was synthesized via a condensation reaction between S-benzylditihocarbazate (SBDTC) and isatin. The produced ligand was reacted with nickel(II) acetate salt in 1:2 (metal:ligand) ratio to yield a brown Ni(SBISA)2 complex (2) (SBISA = monoanionic form of HL1). Characterization of HL1 and its Ni(II) complex was performed via elemental analysis, FT-IR, ICP-AES, UV-Vis spectroscopy and mass spectrometry, along with molar conductivity and magnetic susceptibility measurement. Slow evaporation of 2 from DMSO at room temperature led to a structure crystallizing in the monoclinic P21/a space group with a = 18.6860(3), b = 11.3037(2), c = 19.8993(3), b = 112.1897(10), V = 3891.86(11) Å3, wR2 (all data) = 0.0407 and R1 = 0.0386 for data with I > 2σ(I). The nickel(II) metal center is ligated by doubly-deprotonated NOS monoanionic tridentate HL1 ligands forming a neural distorted octahedral Ni(SBISA)2×2DMSO (2a) complex. The antimicrobial assays of both compounds were performed on selected pathogenic bacteria and fungi strains. HIGHLIGHTS Octahedral Ni(II) complex was synthesized using acetate salt Compound was characterized via physico-chemical analyses Structural studies were resolved via single crystal X-ray diffraction Compound 2a crystallized in a monoclinic system (P21/a space group) with cell parameters a = 18.6860 (3), b = 11.3037 (2), c = 19.8993(3), b = 112.1897 (10), V = 3891.86 (11) Å3, wR2 (all data) = 0.0407 and R1 = 0.0386 for data with I > 2σ(I) Compound was evaluated for its antimicrobial activity GRAPHICAL ABSTRACT